A Group Intervention Using a Self-Regulated Strategy Development (SRSD) Model for Improving Story Writing: Elementary School Students With Autism Spectrum Disorders - TANJI, TAKAYUKI; YOKOTA, TOMOKO (The Japanese Journal of Educational Psychology, 2017)
Recently, writing interventions for students with developmental disorders that use a self-regulated strategy development (SRSD)model have attracted attention. The present study examined effects of a group intervention based on a self-regulated strategy development approach with 6 Japanese 3rd-and 4th-grade students with autism spectrum disorder. The intervention effects were investigated using a one-group pretest-posttest design. The writing performances of story elements and the holistic quality of the stories were assessed. After the students had been taught the strategy, analysis of the writings by 5 of the students suggested that the intervention had been very effective with a number of story elements, and those by 4 of the students showed very effective scores on holistic quality. These results suggest that learning planning and self-monitoring strategies for writing, and the students' learning strategy efficacy, had positive effects on their writing performance. Moreover, the results suggest the efficacy of learning conjunctive phrases, using materials based on the students' interests, self-evaluation, video modeling, peer modeling through this group intervention, and modifying lessons according to the individual characteristics of the students. The discussion deals with the development of a self-regulated strategy development approach model in which practitioners consider students' individual characteristics and whether lessons should be modified for each student.